2020
DOI: 10.1016/j.ijid.2020.08.049
|View full text |Cite
|
Sign up to set email alerts
|

Clusters of COVID-19 associated with Purim celebration in the Jewish community in Marseille, France, March 2020

Abstract: We investigated possible COVID-19 epidemic clusters and their common sources of exposure that led to a sudden increase in the incidence of COVID-19 in the Jewish community of Marseille between March 15 and March 20, 2020. Methods: All data were generated as part of routine work at Marseille university hospitals. Biological diagnoses were made by RT-PCR testing. A telephone survey of families in which a laboratory confirmed case was diagnosed, was conducted to determine possible exposure events. Results: As of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…The remaining two articles were preprints [ 32 , 33 ]. Among the included studies, those that demonstrated a potential role of ski areas in the spread of COVID-19 (n = 7), referred only to the first epidemic wave (February–March 2020) [ 27 , 28 , 29 , 30 , 31 ]. The majority of collected evidence was based on reports from Western Europe, with only one preprint by McLaughlin et al [ 33 ] addressing the pandemic in North America.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The remaining two articles were preprints [ 32 , 33 ]. Among the included studies, those that demonstrated a potential role of ski areas in the spread of COVID-19 (n = 7), referred only to the first epidemic wave (February–March 2020) [ 27 , 28 , 29 , 30 , 31 ]. The majority of collected evidence was based on reports from Western Europe, with only one preprint by McLaughlin et al [ 33 ] addressing the pandemic in North America.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, an index case in France, Contamines-Monjioie, initiated clusters in Spain (Mallorca) and the United Kingdom (London) [ 30 ], whereas another index case in Austria (Ischgl) was linked to clusters in Germany, Norway, Denmark and Iceland [ 29 ]. In another study, where the index case was located in the French Alps, infection spread to Marseille [ 27 ]. However, only in some of these cases it was possible to document a transmission route.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In-person public gathering is one of the most essential components of worship in all Christian denominations as well as in most non-Christian religions. During the COVID-19 pandemic, research has shown that mass religious events linked to worship and holidays played an important role in the initial spread of the SARS-CoV-2 infection (Aherfi et al, 2020;James et al, 2020;Pung et al, 2020;Vermeer & Kregting, 2020;Yezli & Khan, 2020). Certain faith-based communities resisted the efforts of the state agencies to limit religious gatherings (Hill et al, 2020).…”
Section: Challenges For Church and Societymentioning
confidence: 99%
“…There is now published evidence of transmission of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) at relatively small gatherings of people, including weddings (Yusef et al, 2020), religious meetings (Gerbaud et al, 2020;Aherfi et al, 2020;Che Mat et al, 2020]), and festivals (Brandl et al, 2020;Cuschieri et al, 2020) (Table 1). The Grand Magal took place on October 6, 2020, in Touba, Senegal.…”
mentioning
confidence: 99%